Estimation of the tensile modulus of polymer carbon nanotube nanocomposites containing filler networks and interphase regions by development of the Kolarik model. Issue 42 (29th June 2018) - Chen, Shenggui; Sarafbidabad, Mohsen; Zare, Yasser; Rhee, Kyong Yop
Abstract : The Kolarik model for the tensile modulus of co-continuous blends is developed for polymer/carbon nanotube (CNT) nanocomposites assuming continuous CNT networks and the reinforcing and percolating efficiencies of the interphase. Abstract : In this paper, the Kolarik model for the tensile modulus of co-continuous blends based on cross-orthogonal skeleton structures is simplified and developed for polymer/carbon nanotube (CNT) nanocomposites assuming continuous CNT networks in the polymer matrix and the reinforcing and percolating efficiencies of the interphase. For this purpose, the Ouali model for the modulus of nanocomposites above the percolation threshold is linked with the Kolarik model and the interphase percolation is considered with the excluded volume of the nanoparticles. In addition, the simplified Kolarik model is developed with the interphase as a new phase surrounding the nanofiller. A good agreement between the experimental data and the predictions is observed in the samples containing interphases and filler networks, while the developed model cannot estimate the modulus in the absence of interphases and network structures. The developed model demonstrates the effects of all the parameters on the modulus. The interphase parameters more significantly affect the modulus compared to the concentration and modulus of the filler, demonstrating the importance of the interphase properties.